NT-PGC-1α deficiency attenuates high-fat diet-induced obesity by modulating food intake, fecal fat excretion and intestinal fat absorption - Jihyun Kim (Nature Portfolio, 2021)
Abstract Transcriptional coactivator PGC-1α and its splice variant NT-PGC-1α regulate metabolic adaptation by modulating many gene programs. Selective ablation of PGC-1α attenuates diet-induced obesity through enhancing fatty acid oxidation and thermogenesis by upregulation of NT-PGC-1α in brown adipose tissue (BAT). Recently, we have shown that selective ablation of NT-PGC-1α reduces fatty acid oxidation in BAT. Thus, the objective of this study was to test our hypothesis that NT-PGC-1α−/− mice would be more prone to diet-induced obesity. Male and female NT-PGC-1α+/+ (WT) and NT-PGC-1α−/− mice were fed a regular chow or 60% high-fat (HF) diet for 16 weeks. Contrary to our expectations, both male and female NT-PGC-1α−/− mice fed HFD were protected from diet-induced obesity, with more pronounced effects in females. This lean phenotype was primarily driven by reduced dietary fat intake. Intriguingly, HFD-fed female, but not male, NT-PGC-1α−/− mice further exhibited decreased feed efficiency, which was closely associated with increased fecal fat excretion and decreased uptake of fatty acids by the intestinal enterocytes and adipocytes with a concomitant decrease in fatty acid transporter gene expression. Collectively, our results highlight the role for NT-PGC-1α in regulating whole body lipid homeostasis under HFD conditions.